👤

calculati 
[tex] \frac{( \sqrt{2} -1) ^{-1} }{1+ \sqrt{2} } [/tex]
b)[tex] \frac{3 ^{-10}*9 ^{8} }{(-3) ^{2} } [/tex]
c)[tex] \frac{4 ^{-2}*8 ^{-6} }{2 ^{-22} } [/tex]
d)[tex] \frac{5 ^{-5} *25 ^{-10} }{125 ^{3} } [/tex]
e)[tex] \frac{(2 ^{3}) ^{5}*(2 ^{-6} ) ^{2} }{4 ^{2} } [/tex]
f)[tex] \frac{(3 ^{-2})*9 ^{4} }{(3 ^{3} ) ^{3} }[/tex]
g)[tex] \frac{2 ^{-3}*4 ^{3} }{8 ^{-2} } [/tex]


Răspuns :

1/(√2-1)(√2+1)=1/(2-1)=1/1=1
3^16/3^10X3²=3^16/3^12=3^4
2^22/2^4X2^18=2^22/2^22=1
1/5^9X5^5X5^20=1/5^34=5^-34
(2^15.1/2^12)/2^4=2³/2^4=1/2
(1/3².3^8)/3^9=3^5/3^9=1/3^4=3^-4
(2^6/2^3)/1/2^6=2^9